The Effect of Early Tangential Excision and Split Thickness Skin Graft in Reducing Length of Stay in Burns Patients in Jakarta Islamic Hospital Cempaka Putih - Wardhana, Aditya; Winarno, Gammaditya Adhibarata; Tanjunga, Sanjaya Faisal; Augiani, A. S; Zidna, An’umillah Arini (Lingkar Studi Bedah Plastik Foundation, 2021)
Introduction: Early tangential excision (TE) and split-thickness skin graft (STSG) have increased the outcome in burn patients treated at specialized burn centers. This study was conducted to compare the length of stay (LOS) in burn patients undergoing early TE & STSG and delayed TE & STSG. Method: This is a retrospective cross-sectional study including 42 patients with varied burn degrees, and TBSA admitted to Jakarta Islamic Hospital Cempaka Putih (JIHCP) Burn Unit. Patients were assigned to two study groups, the early TE & STSG group including 32 patients and the delayed TE & STSG group including 10 patients. All data were collected from the medical record and compared between two study groups. Result: The mean of LOS in a group with early TE & STSG was shorter (9.81±6.41 days) than LOS in the delayed TE & STSG group (15.80±5.67 days). The data of LOS between these groups were compared using an independent T-test. The LOS in the early TE & STSG group was significantly shorter than the delayed TE & STSG group (p=0.012). Conclusion: In patients with burn injuries, early TE & STSG is associated with a shorter length of stay than the delayed TE & STSG. Our study indicates that early excision within five days after burn injury is optimal to reduce the length of stay in burn patients.